2D Heterostructures: Monolayer Epitaxial Heterostructures for Selective Visible‐Light‐Driven Photocatalytic NO Oxidation (Adv. Funct. Mater. 15/2019). (9th April 2019) - Wang, Liang; Xu, Kang; Cui, Wen; Lv, Dongdong; Wang, Li; Ren, Long; Xu, Xun; Dong, Fan; Dou, Shi Xue; Hao, Weichang; Du, Yi
Abstract : The unique structural and electronic properties of 2D heterostructures have prompted intense exploration in the search for new energy conversion applications. In article number1808084, Xun Xu, Weichang Hao, Yi Du, and co‐workers, report a surface anion exchange strategy to produce scalable 2D bismuth‐based vertical heterostructures with tunable electronic structures and controllable surface active sites. It paves a promising way to develop novel 2D heterostructures for eliminating NO and organics under visible‐light irradiation.